Congenital X‐linked neutropenia with myelodysplasia and somatic tetraploidy due to a germline mutation in SEPT6. Issue 1 (3rd November 2021) - Renella, Raffaele; Gagne, Katelyn; Beauchamp, Ellen; Fogel, Jonathan; Perlov, Aleksej; Sola, Mireia; Schlaeger, Thorsten; Hofmann, Inga; Shimamura, Akiko; Ebert, Benjamin L.; Schmitz‐Abe, Klaus; Markianos, Kyriacos; et al.
Abstract: Septins play key roles in mammalian cell division and cytokinesis but have not previously been implicated in a germline human disorder. A male infant with severe neutropenia and progressive dysmyelopoiesis with tetraploid myeloid precursors was identified. No known genetic etiologies for neutropenia or bone marrow failure were found. However, next‐generation sequencing of germline samples from the patient revealed a novel, de novo germline stop‐loss mutation in the X‐linked gene SEPT6 that resulted in reduced SEPT6 staining in bone marrow granulocyte precursors and megakaryocytes. Patient skin fibroblast‐derived induced pluripotent stem cells (iPSCs) produced reduced myeloid colonies, particularly of the granulocyte lineage. CRISPR/Cas9 knock‐in of the patient's mutation or complete knock‐out of SEPT6 was not tolerated in non‐patient‐derived iPSCs or human myeloid cell lines, but SEPT6 knock‐out was successful in an erythroid cell line and resulting clones revealed a propensity to multinucleation. In silico analysis predicts that the mutated protein hinders the dimerization of SEPT6 coiled‐coils in both parallel and antiparallel arrangements, which could in turn impair filament formation. These data demonstrate a critical role for SEPT6 in chromosomal segregation in myeloid progenitors that can account for the unusual predisposition to aneuploidy and dysmyelopoiesis.